1995
DOI: 10.1111/j.1440-1630.1995.tb01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian occupational therapy research: A review of publications 1987–91

Abstract: The aim of this study was to describe the characteristics of Australian occupational therapy research published during the period 1987–91. A literature review of the Australian Occupational Therapy Journal for the years 1987–91, and the Australian Association of Occupational Therapists' conference proceedings for the years 1988 and 1991 was conducted. A number of trends were identified. The proportion of research journal articles and conference papers over the 5 year period remained stable. Most journal resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Likewise, Cusick (1995) analyzed the publications in AOTJ from 1987 to 1991 and found only 42% of the publications could be classified as research based. More recently, Gutman (2011) examined AJOT from 2008 to 2011 and found that studies testing treatment effectiveness and rigor of experimental design had steadily increased; however, examination of practice efficacy was lacking.…”
mentioning
confidence: 99%
“…Likewise, Cusick (1995) analyzed the publications in AOTJ from 1987 to 1991 and found only 42% of the publications could be classified as research based. More recently, Gutman (2011) examined AJOT from 2008 to 2011 and found that studies testing treatment effectiveness and rigor of experimental design had steadily increased; however, examination of practice efficacy was lacking.…”
mentioning
confidence: 99%
“…The most common qualitative research design used was grounded theory, with 15.4% (n 5 6) of AJOT studies reporting its use. ; and Cusick (1995) all observed that the level of rigor and methodological sophistication of occupational therapy studies being published in journals is increasing.…”
Section: Instrument Development and Testing And Effectiveness Studiesmentioning
confidence: 99%
“…Several content reviews of AOTJ articles have been published previously (e.g. Bell & Anderson, ; Cusick, ; Madill, Brintnell & Stewin, ; Ziviani, Behan & Rodger, ). Ziviani et al .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 78 articles from each 5‐year period were examined and it was noted that articles increasingly addressed professional promotion in the wider community and there was a need for a unifying Australian occupational therapy conceptual framework. Cusick described the traits of occupational therapy research literature published from 1987 to 1991 by conducting a literature review of AOTJ and the Australian Association of Occupational Therapists' conference proceedings. It was determined that the proportion of research articles published in AOTJ and presented at national conferences remained consistent during the 5‐year period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation